Radiation power spectral distribution of two electrons moving in magnetic fields - Konstantinovich, A.V.; Melnychuk, S.V.; Konstantinovich, I.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
Integral expressions for spectral distributions of the radiation power for systems of non-interacting point charged particles moving on arbitrary trajectory in electromagnetic fields in isotropic transparent media and in vacuum are investigated using the Lorentz self-interaction method. Special attention is given to the research of the fine structure of the synchrotron radiation spectral distribution of two electrons spiraling in vacuum in a relativistic case. The spectra of synchrotron, Cherenkov and synchrotron-Cherenkov radiations for a single electron are analyzed.